Social context shapes cognitive abilities: associative memories are modulated by fight outcome and social isolation in the crab Neohelice granulata - Santos, María Jimena (2021)
Cognitive abilities of an animal can be influenced by distinct social experiences. However, the extent of this modulation has not been addressed in different learning scenarios: are all tasks similarly affected by social experiences? In the present study, we analyzed the effect of social dominance in aversive and appetitive memory processes in the crab Neohelice granulata. In addition, we studied the influence of social isolation on memory ability. Social dominance experiments consisted of an agonistic phase immediately followed by a memory phase. During the agonistic phase, matched pairs of male crabs were staged in 10-min encounters and the dominant or subordinate condition of each member of the dyad was determined. During the memory phase, crabs were trained to acquire aversive or appetitive memory and tested 24 h later. Results showed that the agonistic encounter can modulate long-term memory according to the dominance condition in such a way that memory retention of subordinates results higher than their respective dominant. Remarkably, this result was found for both aversive and appetitive memory tasks. In addition, we found that isolated animals showed no memory retention when compared with animals that remained grouped. Altogether this work emphasizes the importance of social context as a modulator of cognitive abilities.